IMPLEMENTASI KEBIJAKAN RETRIBUSI IZIN USAHA PERIKANAN DI KABUPATEN BANGGAI KEPULAUAN - Mahmuddin, Afandi (Katalogis, 2017)
This study aimed to determine the implementation of fishery business license retribution policy in Banggai Islands Regency. The method used was descriptive qualitative research method and data were collected through observation, interviews, and documentation, with purposive informant selection resulting in 7 people. The results, with the approach of the implementation model of George Edward III, showed that the implementation of fishery business license retribution policy in Banggai Islands Regency had not been running well because from the four aspects studied in the field, there were three aspects which were not running well. The implementation of the program was known from the influencing factors, namely: 1) Communication about the contents of Local Regulation Number 12 Year 2012 on Fishery Business License Retribution in Banggai Islands Regency had been implemented properly. 2) Resources in the implementation of Local Regulation Number 12 Year 2012 on Fishery Business License Retribution in Banggai Islands Regency were inadequate. 3) The attitude of the implementers of fishery business license retribution policy in Banggai Islands Regency had not shown good commitment. 4) The bureaucratic structure in the implementation of fishery business license retribution policy according to the standard operating procedures (SOP) had not been implemented properly.